Covalent organic framework nanofluidic membrane as a platform for highly sensitive bionic thermosensation - Pengcheng Zhang (Nature Portfolio, 2021)
Efforts have been devoted to fabricating artificial membranes that can mimic biological functions but the design of a bionic thermometer remains in its infancy. Herein, the authors report a nanofluidic membrane based on an ionic covalent organic framework capable of monitoring temperature variations and expressing it in the form of continuous potential differences.